Metabolic and Performance Responses to Carbohydrate Intake During Exercise - Aragón Vargas, Luis Fernando (2000)
During exercise, an adequate supply of substrates is required for the continuing resynthesis of ATP in working muscles. Muscle fibers have limited stores of creatine phosphate, glycogen, and triglycerides and so must also be able to extract glucose and free fatty acids from the blood to meet the overall energy needs of the contracting fiber. Oxidization of protein usually makes only a small contribution to energy production, although protein can be an important source of energy under extreme circumstances. To maintain the homeostasis and to assure that adequate fuel is available to sustain contraction of muscle fibers, utilization of carbohydrate, fatty acids, and protein is carefully balanced by an orchestra of hormones and enzymes. An adequate supply of carbohydrate (in the form of blood glucose and muscle glycogen) is clearly related to exercise performance. Human performance involves a variety of biomechanical, physiological, and psychological factors. From a physiological point of view, performance is strongly related to the ability to produce or sustain a large power output to overcome resistance or drag, while protecting the homeostasis of cells and organ systems.1 Maintaining a given power output requires an appropriate supply of energy to the working muscle fibers and, as explained below, this requires the availability of carbohydrate as fuel. Because carbohydrate stores in the human body are not very large (about 300-to-500 grams), and because carbohydrate is a predominant fuel during many types of exercise, ingestion of various forms of carbohydrate before, during, and after exercise has been systematically studied as a means of extending that fuel supply for a longer period of time. This research has repeatedly shown an improvement in exercise performance. Understanding the metabolic and performance responses to carbohydrate intake during exercise is critical in understanding one important aspect of sports drink efficacy: the ability of the beverage to improve exercise performance. For this reason, this chapter will focus on the metabolic and performance effects of carbohydrate consumption during exercise with special attention devoted to recent research on the effects of consuming sports drinks during intermittent, high-intensity exercise.